Lidocaine carboxymethylcellulose with gelatine co-polymer hydrogel delivery by combined microneedle and ultrasound - Atul Nayak; Hiten Babla; Tao Han; Diganta Das (2014)
A study that combines microneedles (MNs) and sonophoresis pre-treatment was explored to determine their combined effects on percutaneous delivery of lidocaine from a polymeric hydrogel formulation. Varying ratios of carboxymethylcellulose and gelatine (NaCMC/gel ranges 1:1.60–1:2.66) loaded with lidocaine were prepared and characterized for zeta potential and particle size. Additionally, variations in the formulation drying techniques were explored during the formulation stage. Ex vivo permeation studies using Franz diffusion cells measured lidocaine permeation through porcine skin after pre-treatment with stainless steel MNs and 20 kHz sonophoresis for 5-and 10-min durations. A stable formulation was related to a lower gelatine mass ratio because of smaller mean particle sizes and high zeta potential. Lidocaine permeability in skin revealed some increases in permeability from combined MN and ultrasound pre-treatment studies. Furthermore, up to 4.8-fold increase in the combined application was observed compared with separate pre-treatments after 30 min. Sonophoresis pre-treatment alone showed insignificant enhancement in lidocaine permeation during the initial 2 h period. MN application increased permeability at a time of 0.5 h for up to 17 fold with an average up to 4 fold. The time required to reach therapeutic levels of lidocaine was decreased to less than 7 min. Overall, the attempted approach promises to be a viable alternative to conventional lidocaine delivery methods involving painful injections by hypodermic needles. The mass transfer effects were fairly enhanced and the lowest amount of lidocaine in skin was 99.7% of the delivered amount at a time of 3 h for lidocaine NaCMC/GEL 1:2.66 after low-frequency sonophoresis and MN treatment.